Christological Evaluation Of Inculcivism Theology - Goktondi Pasaribu; Corinthians Joel Sangian; Oktavia Kristika Sari (Theological Journal Kerugma, 2020)
Inclusivism is defined as a mindset that recognizes that Jesus' liberation mission is addressed to every human being without exception. As a result, each and every person has the right to salvation and release. This theology does not want to be viewed as cruel by exclusivism, but neither does it want to be regarded as rejecting Christ's uniqueness by pluralism, thus it chooses the middle ground, namely inclusivism. This study employs qualitative special literature on verses like as John 3:8, 1 Timothy 2:4, 1 John 4:7-8, and Acts 10:22, which are utilized by Inclusivism as the foundation for their Christological beliefs. The Inclusivist Trinitarian Christology undermines the idea of Christ as a Special Revelation because it obscures the privilege of Christ as Revelation (John 1:1) and the Bible as a Special Revelation by the Holy Spirit's inspiration by 'perpetuating the News of Christ' in order to remain available to everyone throughout all centuries.